2021
DOI: 10.1007/s00784-021-04185-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative visualization of the lingual nerve by 3D double-echo steady-state MRI in surgical third molar extraction treatment

Abstract: Objectives To assess the lingual nerve (LN) visualization using a 3D double-echo steady-state MRI sequence (3D-DESS). Materials and methods Three readers prospectively evaluated the LN for its continuous visibility in 3D-DESS MRI in 19 patients with an indication for removal of mandibular impacted third molars, using a 5-point scale (4 = excellent to 0 = none). Six LN anatomical intermediate points (IP) were selected and checked for their detectability by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…In this context, new developments target novel MRI protocols modified for dental applications, such as 3D-DESS and 3D short-tau inversion recovery (STIR), which enable high-resolution and high-contrast reliable assessment of the MTM region [ 23 ]. In addition to simultaneous visualization of bone and soft tissues, it is possible to visualize the positional relationship between the IAN/LN and MTM [ 18 ], to precisely determine the localization of the IAN within the osseous boundaries of the mandibular canal [ 14 ], and to visualize the lingual nerve up to its insertion into the tongue both focally and continuously [ 12 ]. In these dedicated black bone MRI protocols, the free induction decay (FID) signals of fast imaging with steady-state precession (FISP) are combined with the echo signal of a time-reversed FISP (PSIF), reducing signal dropout due to dephasing while simultaneously increasing its T2* specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, new developments target novel MRI protocols modified for dental applications, such as 3D-DESS and 3D short-tau inversion recovery (STIR), which enable high-resolution and high-contrast reliable assessment of the MTM region [ 23 ]. In addition to simultaneous visualization of bone and soft tissues, it is possible to visualize the positional relationship between the IAN/LN and MTM [ 18 ], to precisely determine the localization of the IAN within the osseous boundaries of the mandibular canal [ 14 ], and to visualize the lingual nerve up to its insertion into the tongue both focally and continuously [ 12 ]. In these dedicated black bone MRI protocols, the free induction decay (FID) signals of fast imaging with steady-state precession (FISP) are combined with the echo signal of a time-reversed FISP (PSIF), reducing signal dropout due to dephasing while simultaneously increasing its T2* specificity.…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional radiographic imaging techniques can only visualize the IAN indirectly via the osseous boundaries of the mandibular canal, whereas the nervous tissue of the IAN and LN per se cannot be depicted directly. For this purpose, magnetic resonance imaging (MRI), with the recently introduced black-bone MRI sequences, can simultaneously visualize osseous structures and neural tissue in the oral cavity with high spatial resolution and excellent soft-tissue contrast [ 11 , 12 , 13 , 14 ]. Although most LN and IAN injuries recover spontaneously, therapy should be initiated early in selected cases with evident nerve damage, although the literature is inconsistent regarding the therapeutic time window [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of black bone MRI sequences in their application in the dental field confirmed that they are best suited to overcome the limitations of hard tissue imaging in oral and maxillofacial radiology [ 12 , 17 , 33 ]. The STIR sequence offered the best signal-to-noise ratio and contrast-to-noise ratio between nerves and muscles, while the DESS protocols were suitable for comparing quantitative parameters [ 17 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of black bone MRI sequences in their application in the dental field confirmed that they are best suited to overcome the limitations of hard tissue imaging in oral and maxillofacial radiology [ 12 , 17 , 33 ]. The STIR sequence offered the best signal-to-noise ratio and contrast-to-noise ratio between nerves and muscles, while the DESS protocols were suitable for comparing quantitative parameters [ 17 , 33 ]. For visualization of more complex medical diseases, especially space-occupying malignant lesions, the contrast-enhanced 3D SPACE STIR sequence could accurately detect the localization of the pathological process with higher spatial resolution and image quality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation